PENGARUH MEDIA TANAM DAN NUTRISI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA KEPALA RENYAH (Lactuca sativa var. capitata) SECARA HIDROPONIK - Astuti, Sri; Yana, Yeni Muly (Konservasi Hayati, 2019)
Study aims to determine the effect of planting media and nutrients on the growth and yield of crispy lettuce (Lactuca sativa var. Capitata) hydroponically and to determine the best planting media and types of nutrients on the growth and yield of crispy lettuce (Lactuca sativa) var. capitata) hydroponically. This research uses factorial experimental design in CRD. The first factor is 3 planting media (coffee husk charcoal, rice husk charcoal and rock wool). The second factor is 3 nutrients (organic, AB mix and organic + inorganic). There are 9 combinations of planting media and nutrition for the growth of crispy lettuce head planting. Each combination is randomized before being tested, to determine the order of testing. Each combination is done 3 times. The results of observations and average calculation of plant parameter data at the 4th week after transplanting showed the result that there was no effect of the planting media and nutrients on the growth and yield of lettuce. Likewise with the results of analysis of variance (ANOVA) showed that there was no real effect on plant parameters.